1968
DOI: 10.1002/rds196837715
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Effects of Energetic Electrons at the 6.6 Re Equator and the Auroral Zone During Magnetospheric Substorms

Abstract: During magnetically disturbed times, large intensity variations are observed for electrons of energies 50· to 150-ke V at the geostationary orbit of the ATS-1 satellite. Simultaneously, the correlation experiment at the magnetic conjugate region of the satellite has shown that large fluxes of brems· strahlung X-rays from precipitated energetic electrons are observed on high-altitude balloons while magnetic bays are recorded on the ground. The conclusion reached is that the magnetospheric substorm is responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1968
1968
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Note that the second injection pulse was also closely accompanied by a large increase in the NAR riometer intensity. Hence the ground-based riometer trace mirrors almost precisely the shape of the equatorial flux profile measured for electrons on the conjugate field line [see Parks et al, 1968;Rosen and Winckler, 1970].…”
Section: Moderate Precipitation Eventsmentioning
confidence: 76%
“…Note that the second injection pulse was also closely accompanied by a large increase in the NAR riometer intensity. Hence the ground-based riometer trace mirrors almost precisely the shape of the equatorial flux profile measured for electrons on the conjugate field line [see Parks et al, 1968;Rosen and Winckler, 1970].…”
Section: Moderate Precipitation Eventsmentioning
confidence: 76%
“…Studies conducted have shown a broad correlation between geosynchronous electron flux intensity and CNA during substorms (e.g. Parks et al, 1968;Arnoldy and Chan, 1969;Rosen and Winckler, 1970). Baker et al (1981) present a number of events where riometers record CNA rises at the time of geosynchronous flux intensity increases at conjugate LANL satellites during the near midnight and morning sectors, again during substorms.…”
Section: Precipitation Following the Substorm Activitymentioning
confidence: 99%
“…[2] The acceleration of charged particles to suprathermal energies and the resulting flux increases of high-energy particles are a major consequence of space plasma activity and magnetic reconfiguration. Energetic particle events in the Earth's magnetotail (injections) are typically associated with magnetospheric substorms [e.g., Parks et al, 1968;Lezniak et al, 1968;Arnoldy and Chan, 1969;Baker et al, 1978;Belian et al, 1981] or, more generally, dipolarization events [e.g., Nakamura et al, 2002;Runov et al, 2009;Sergeev et al, 2009;Deng et al, 2010], characterized by a rapid change from stretched, tail-like to more dipolar magnetic fields. Dipolarization events may involve a brief earthward moving dipolarization pulse or "dipolarization front" [e.g., Nakamura et al, 2002;Runov et al, 2009;Sergeev et al, 2009] or, typically closer to Earth, an increase of B z toward a more persistent higher level .…”
Section: Introductionmentioning
confidence: 99%